Amine Borane Based Hydrogen Carriers: An Evaluation - Müller, Karsten; Stark, Katharina; Müller, Benjamin; Arlt, Wolfgang (Energy & Fuels, 2012)
Liquid organic hydrogen carriers (LOHCs) represent a new concept for energy-storage. LOHCs are able to store a considerable amount of hydrogen and release it on demand without being consumed themselves. A variety of different substances has been proposed recently. One promising group of potential carriers is amine borane based compounds. This contribution introduces the LOHC concept and gives a review over the amine borane based hydrogen carriers. An energetical evaluation using Aspen Plus was performed, and overall efficiencies were calculated. An energy storage system based on azaborines reaches efficiencies of up to 30%. This study shows that still intensive research on synthesis, regeneration, long-term stability, liquefaction, and toxicity is needed before this technique is marketable.

Energy storage in residential and commercial buildings via Liquid Organic Hydrogen Carriers (LOHC) - Teichmann, Daniel; Stark, Katharina; Müller, Karsten; Zöttl, Gregor; Wasserscheid, Peter; Arlt, Wolfgang (Energy and Environmental Science, 2012)
This contribution proposes the usage of Liquid Organic Hydrogen Carriers (LOHC) for the establishment of a decentralised energy storage network. Due to the continually increasing amount of renewable energy within the power grid, in particular in countries of the European Union, a huge demand for storage capacities develops that can hardly be met by large-scale systems alone. Because of their high storage density and good manageability LOHC substances permit the local storage of excess energy in residential and commercial buildings. Following the approach of a CHP system ('combined heat and power' or more precisely a 'combined heat and storage' system), thermal losses from the storage processes can be used for heating (and cooling) purposes in order to increase the overall efficiency. An evaluation of the economic feasibility identifies possible approaches to generate income from storage operation. The usage of exhaust heat for heating proves to significantly support the business case by providing a considerable financial contribution that is usually not exploitable for centralised storage units. © 2012 The Royal Society of Chemistr
WiSo-Import:2015-03-26:5048

Experimental assessment of the degree of hydrogen loading for the dibenzyl toluene based LOHC system - Müller, Karsten; Aslam, Rabya; Fischer, Armin; Stark, Katharina; Wasserscheid, Peter; Arlt, Wolfgang (International Journal of Hydrogen Energy, 2016)
Liquid Organic Hydrogen Carriers allow for storing hydrogen with high density at ambient conditions. In the LOHC hydrogen storage process, a significant number of different partially and fully hydrogenated species occur on the reaction pathway from the hydrogen-lean to the hydrogen-rich form of the LOHC system. In order to access the amount of hydrogen stored in the carrier system, ways of measuring the degree of hydrogenation are required. A number of physical properties can be correlated with the degree of hydrogenation. However, there are different mixtures of hydrogenated, partly hydrogenated and dehydrogenated derivatives which result in an identical degree of hydrogenation but different properties. In this contribution we report on attempts to correlate physico-chemical properties and spectroscopic data to the degree of hydrogenation of the dibenzyl toluene system by using density, viscosity, refractive index, UV–VIS and Raman spectroscopy measurements. The most reliable correlations were found for density or refractive index.
Keywords: Fuel gauge; Hydrogen storage; LOHC; Online measurement; Organic hydrides

Hydrogen Storage: Thermochemical Studies of N-Alkylcarbazoles and Their Derivatives as a Potential Liquid Organic Hydrogen Carriers - Emel'Yanenko, Vladimir N.; Varfolomeev, Mikhail A.; Verevkin, Sergey P.; Stark, Katharina; Müller, Karsten; Müller, Michael; Bösmann, Andreas; Wasserscheid, Peter; Arlt, Wolfgang (Journal of Physical Chemistry C, 2015)
Although N-ethylcarbazole is considered as a most promising potential liquid organic hydrogen carriers (LOHC) substance, a major drawback for stationary and particularly mobile applications is its high melting point of 343 K. Study of other possible N-alkylcarbazole-derivatives having lower melting points but keeping a high storage density is of practical importance. This contribution presents thermochemical properties (enthalpy of formation, enthalpy of vaporization, enthalpy of sublimation, and fusion enthalpy) for N-alkylcarbazoles (with alkyl = isopropyl, n-propyl, and n-butyl) derived from experiments in order to investigate the applicability of the carbazole derivatives as potential LOHCs. Additionally, high-level quantum chemical calculations were applied to determine molar enthalpies of formation of the gaseous carbazole derivatives and thus validated the experimental findings. Using a combination of the quantum-chemical calculations with vaporization enthalpy data measured in this work, the standard molar liquid phase enthalpies of formation were derived for alkylcarbazole derivatives. Results of this study were applied for thermodynamic analysis of the liquid-phase reversible hydrogenation/dehydrogenation processes with N-alkylcarbazoles.

Liquid organic hydrogen carriers: An upcoming alternative to conventional technologies. Thermochemical studies. - Verevkin, Sergey P.; Emel'Yanenko, Vladimir N.; Heintz, Andreas; Stark, Katharina; Arlt, Wolfgang (Industrial & Engineering Chemistry Research, 2012)
A system based on the catalytic hydrogenation/dehydrogenation reactions of N-ethylcarbazole is one of the most promising as the new class of the liquid organic hydrogen carrier (LOHC) compounds. Enthalpy of formation of the liquid dodecahydro-N-ethylcarbazole (fully hydrogenated N-ethylcarbazole) was measured using combustion calorimetry. Vaporization enthalpy for this compound was derived from vapor pressure-temperature dependence measured by transpiration. The enthalpy of formation of the gaseous dodecahydro-N-ethylcarbazole was derived and validated with the high-level quantum chemical calculation. Vapor pressures of the liquid N-ethylcarbazole (0.0008 bar) and dodecahydro-N- ethylcarbazole (0.01 bar) at a practical and relevant temperature (400 K) were assessed from the new experimental data. It has turned out that these vapor pressures were low enough to fulfill the basic requirement for an LOHC. © 2012 American Chemical Society.

Liquid Organic Hydrogen Carriers: Thermophysical and Thermochemical Studies of Benzyl- and Dibenzyl-toluene Derivatives - Müller, Karsten; Stark, Katharina; Emel'Yanenko, Vladimir N.; Varfolomeev, Mikhail A.; Zaitsau, Dzmitry H.; Shoifet, Evgeni; Schick, Christoph; Verevkin, Sergey P.; Arlt, Wolfgang (Industrial & Engineering Chemistry Research, 2015)
The heat transfer oils dibenzyltoluene and benzyltoluene are promising materials as a new class of liquid organic hydrogen carrier compounds (LOHC). Thermophysical properties (heat capacity, density, viscosity, and surface tension) of the commercially available thermofluids Marlothem LH (benzyltoluene) and Marlotherm SH (dibenzyltoluene) and their completely hydrogenated derivatives were measured. Thermochemical properties (enthalpies of combustion and enthalpies of vaporization) were derived from experiments. Gas-phase molar enthalpies of formation were derived and validated with group-additivity and high-level quantum chemical calculations. Enthalpies of the hydrogenation/dehydrogenation reactions of the LOHC pairs under study were derived.

Liquid Organic Hydrogen Carriers: Thermophysical and Thermochemical Studies of Carbazole Partly and Fully Hydrogenated Derivatives - Stark, Katharina; Emel'Yanenko, Vladimir N.; Zhabina, Aleksandra A.; Varfolomeev, Mikhail A.; Verevkin, Sergey P.; Müller, Karsten; Arlt, Wolfgang (Industrial & Engineering Chemistry Research, 2015)
Carbazole derivatives are promising liquid organic hydrogen carrier (LOHCs). They can take up and release hydrogen in catalytic hydrogenation/dehydrogenation reactions. The thermophysical properties (heat capacity, density, viscosity, surface tension, and refractive index) of carbazole and N-ethylcarbazole, as well as those of their hydrogenated derivatives, were measured. Furthermore, thermochemical properties (enthalpy of vaporization, sublimation, and fusion) were derived from experiments. Molar enthalpies of formation of the gaseous carbazole derivatives were calculated and validated with high-level quantum chemical calculations. Molar enthalpies of formation data in the liquid phase were derived by combining the high-level quantum chemistry values of the gas-phase enthalpies of formation with experimentally determined enthalpies of vaporization. Thermodynamic analysis of the hydrogenation/dehydrogenation reactions of the carbazole derivatives was performed. This analysis, among others, revealed a rather weak dependence of thermodynamic hydrogen release characteristics on the alkyl chain length. The thermophysical properties of the derivatives show a strong dependence on the degree of hydrogenation. Therefore, the state of hydrogenation should always be considered when dealing with substance properties of LOHCs. Using the data presented in this work, a more reliable process modeling is possible.

Melting Points of Potential Liquid Organic Hydrogen Carrier Systems Consisting of N-Alkylcarbazoles - Stark, Katharina; Keil, Philipp; Schug, Sebastian; Müller, Karsten; Wasserscheid, Peter; Arlt, Wolfgang (Journal of Chemical and Engineering Data, 2016)